FORMULATION OF TABLET FROM PAPAYA AND BAY LEAF EXTRACT WITH VARIATION OF CONCENTRATION POLYVINYLPYRROLIDONE AS A BINDER - Rustiani, Erni; Miranti, Mira; Rahmahuda, Nurul Karima (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Â  Objectives: Extensive studies on the pharmacological activities of papaya and bay leaf exhibit that these plants effectively alleviate degenerative diseases including diabetes. However, herbal drugs from papaya and bay leaf have never been made. The aim of this research was to formulate a tablet from the combination of papaya extract and bay leaf with different concentrations (1%, 2%, and 3%) of polyvinylpyrrolidone (PVP) K30 as a binder using the wet granulation method. Methods: Evaluation of the tablet's physical properties (i.e., weight variation, friability, hardness, disintegration time, and physical appearance) was done using standard methods while total flavonoid in the extracts was determined by the spectrophotometry method. Results: The tablet was light brown and had both flat top and bottom, a specific odor and a bitter taste. The physical properties of the tablet were in accordance with pharmaceutical standards. The total flavonoid content in the papaya and bay leaves extract was 1.562% and 2.240%, respectively. Conclusions: It can be concluded that PVP K-30 concentration can be used as a binder to formulate dry papaya and bay leaf extracts into high-quality and ready-to-consume tablets.